Modal analysis of Lamb waves of steel pipeline with calcium deposits - V. E. Chanchina; A. E. Kondratiev; N. A. Antsupov (Известия высших учебных заведений: Проблемы энергетики)
The relevance of the work lies in the study of the effect of calcium deposits of various thicknesses on the inner walls of the pipeline on the parameters of its own vibrations.OBJECTIVE: To construct a mathematical model of a steel pipeline without deposits and with calcium deposits of various thicknesses on its inner walls. To perform a modal analysis of the natural vibrations of the steel pipeline. Theoretically confirm the dependence of the change in the oscillation frequency of the pipeline when exposed to sediments.METHODS. The paper highlights a method for analyzing the natural frequencies of the pipeline using the acoustic method of non-destructive testing, since it can be implemented with one-way access and does not violate the integrity of the object of control. In solving this problem, the method of mathematical analysis in the software package of finite element analysis was used. results. The article describes the relevance of the topic, discusses the main methods of non-destructive testing, and defines Lamb waves. A mathematical model of a steel pipeline section with out internal deposits and with calcium deposits of 5 different thicknesses has been constructed.CONCLUSION. Calculations have shown that the natural vibration frequencies of the pipeline without deposits and with calcium deposits change in the direction of increasing values, the frequency increase occurs in waves. The highest frequency values are obtained when modeling calcium deposits with a thickness of 10 mm on the walls of the pipeline.